Restructuring of bank loans (Journal of Economic Research & Business Administration, 2016)
Being the most important field of activity of the banks, crediting has asignificant impact on the economic development. At the same time, bank crediting is exposed to a number of factors determining its dynamics and structure. Systemization of these factors and study of their influence on the credit process plays an important role in improving the efficiency of the crediting process and neutralization of its negative aspects. One method of minimization of credit risks of commercial banks is carrying out of restruc- turing procedure. In connection with this, the article describes the features of the restructuring of problem loans by the commercial banks.
Keywords: Restructuring; credit risk; commercial banks; problem loans; collecting companies